The role of fibroblast growth factor 21 in atherosclerosis. (February 2017) - Kokkinos, John; Tang, Shudi; Rye, Kerry-Anne; Ong, Kwok Leung
Abstract: The metabolic properties of the endocrine fibroblast growth factor 21 (FGF21) have been extensively studied in the past decade. Previous studies have demonstrated the lipid-lowering, anti-inflammatory and anti-oxidant properties of FGF21. FGF21 is mainly secreted in the liver and adipose tissue in response to a range of physiological and pathological stimuli. In animal and in vitro studies, FGF21 has been shown to improve lipid profiles and inhibit key processes in the pathogenesis of atherosclerosis. It exerts its effects on the cardiovascular system via adiponectin dependent and independent mechanisms. However, the signalling pathways by which FGF21 exerts its effects on endothelial cells remains unknown and needs to be further investigated. The elevation of circulating FGF21 levels in cardiovascular disease has also raised questions as to whether FGF21 can be used as a biomarker to predict subclinical atherosclerosis and cardiovascular events. Recent findings from population studies must be validated in independent cohorts before FGF21 can be used as a biomarker in the clinical setting. The anti-atherosclerotic effects of FGF21 have been investigated in two recent clinical trials, where treatment with an FGF21 analog significantly improved the cardiometabolic profile in obese patients with type 2 diabetes. This review will evaluate recent advances that suggest there may be a role for FGF21 in atherosclerosis. Highlights: Fibroblast growth factor 21 (FGF21) level is elevated in cardiovascular disease. FGF21 protects against atherosclerosis development and progression. FGF21 improves lipid profiles and reduces vascular inflammation and oxidative stress. FGF21 has been implicated as a biomarker for subclinical atherosclerosis. FGF21 has been suggested to have therapeutic potential in atherosclerosis prevention.